2018
DOI: 10.1021/jacs.7b11639
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Interactome Mapping by Photoaffinity Labeling Reveals Binding Site Hotspots for the NSAIDs

Abstract: Many therapeutics elicit cell-type specific polypharmacology that is executed by a network of molecular recognition events between a small molecule and the whole proteome. However, measurement of the structures that underpin the molecular associations between the proteome and even common therapeutics, such as the nonsteroidal anti-inflammatory drugs (NSAIDs), is limited by the inability to map the small molecule interactome. To address this gap, we developed a platform termed small molecule interactome mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 51 publications
2
90
0
Order By: Relevance
“…Targeted database searching yielded binding site maps of photo-celecoxib (2) to COX-2 in vitro and in the global proteome in Jurkat and K562 cells. 11 In the course of these studies, we found that CuAAC with a standard biotin azide often yielded higher overall anti-biotin signal than CBA 5, which may have been caused by incomplete CuAAC with the small molecule-labeled proteome. Inspired by chelation-assisted catalysis, 13 we thus designed CBPA 6 to improve the throughput of binding site hotspot mapping ( Figure 1D, Scheme S1).…”
mentioning
confidence: 87%
“…Targeted database searching yielded binding site maps of photo-celecoxib (2) to COX-2 in vitro and in the global proteome in Jurkat and K562 cells. 11 In the course of these studies, we found that CuAAC with a standard biotin azide often yielded higher overall anti-biotin signal than CBA 5, which may have been caused by incomplete CuAAC with the small molecule-labeled proteome. Inspired by chelation-assisted catalysis, 13 we thus designed CBPA 6 to improve the throughput of binding site hotspot mapping ( Figure 1D, Scheme S1).…”
mentioning
confidence: 87%
“…Comparison between samples can be achieved using quantification methods (e.g., label‐free, SILAC, tandem mass tag [TMT]). These approaches have been widely used to characterize the protein interactomes of metabolites, fragment libraries, bioactive small molecules, and drugs (Das, ; Flaxman & Woo, ; Gao, Mfuh, Amako, & Woo, ; Gertsik et al., ; MacKinnon, Garrison, Hegde, & Taunton, ; Parker et al., ). Cleavage of the enrichment handle by chemical or enzymatic means then allows for recovery of the small molecule–conjugated peptide for analysis of the binding site itself (Speers & Cravatt, ; Szychowski et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The major steps of the procedure are: (1) generation of small molecule–conjugated proteins either in live cells or cell lysate; (2) attachment of an acid‐cleavable, isotopically coded biotin picolyl azide via CuAAC and enrichment with streptavidin‐agarose beads, followed by collection of trypsin and acid cleavage fractions for protein and conjugation site identification, respectively; and (3) LC‐MS/MS analysis to identify the interacting proteins and conjugated peptides. The example data shown was generated by implementing the SIM‐PAL procedure following treatment of A549 cells with photo‐celecoxib (Gao et al., ; Miyamoto et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biotin portion of the AZO linker is cleaved off upon reduction of the azobenzene group using sodium dithionite resulting in the formation of a residual aminophenol moiety on the cleaved peptide. To date, the applications of the DADPS linker included: identification of glycosylation sites 23 , profiling the deubiquitinase family of proteins 24 , and mapping the sites of small-molecule protein interactions [25][26][27] . The biotin portion of the DADPS linker is cleaved using formic acid leaving a hydroxyl moiety on the peptide adduct.…”
Section: Introductionmentioning
confidence: 99%